TECHNICAL DESIGN OF ELECTRIC BICYCLES AS OPERATIONAL AIDS IN THE AIRPORT FACILITY MAINTENANCE - Martadinata, M Indra; Fatiha, Hana; Soleh, Asep Muhamad; Nugroho, Romi Ario; Rizkyanti, Fadhilla Nina; Setiyo, Setiyo (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Penerbangan Palembang, 2025)
Airports, as the main gateway to air transportation in Indonesia, are increasingly expected to implement environmentally friendly practices, one of which includes the use of electric vehicles to support operational activities. This research aims to design the technical specifications of an electric bicycle as a tool for operational maintenance at airport facilities. The method employed is Research and Development (R&D) using the ADDIE model, supported by a literature review and simulation using SolidWorks 2021. The bicycle is designed with a simple, mild steel frame, a 350-watt BLDC motor, and a 48V 15Ah lithium-ion battery, with a payload capacity of up to 100 kg. Structural analysis using the Finite Element Method (FEM) shows that the design is structurally safe, with Von Mises stress and strain values remaining below the material's yield strength. The safety factor also indicates high structural reliability. The novelty of this study lies in the integration of FEM-based structural design with airport-specific operational requirements, thereby filling a gap in prior research that has primarily focused on general e-bike performance without consideration for the specific context of airport maintenance. With an estimated construction cost of IDR 8 million, the design presents a low-emission, cost-effective solution to support sustainable airport operations.